Projecting Russia in a Mediatized World : Recursive Nationhood - Stephen Hutchings (Routledge, 2022)
This book presents a new perspective on how Russia projects itself to the world. Distancing itself from familiar, agency-driven International Relations accounts that focus on what ‘the Kremlin'is up to and why, it argues for the need to pay attention to deeper, trans-state processes over which the Kremlin exerts much less control. Especially important in this context is mediatization, defined as the process by which contemporary social and political practices adopt a media form and follow media-driven logics. In particular, the book emphasizes the logic of the feedback loop or ‘recursion', showing how it drives multiple Russian performances of national belonging and nation projection in the digital era. It applies this theory to recent issues, events, and scandals that have played out in international arenas ranging from television, through theatre, film, and performance art, to warfare.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.